2023
DOI: 10.3390/pathogens12010127
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol; Effective Anthelmintic Compound against Foodborne Parasite Trichinella spiralis Muscle Larvae and Adult

Abstract: Trichinosis is a foodborne parasitic infection that results from ingestion of raw or under-cooked pork meat infected by parasitic nematode Trichinella spiralis with cosmopolitan distribution. Anthelmintic drugs are used to eliminate intestinal adult parasites and larvae as well as tissue-migrating newborn and in-turn encysted larvae. However, eliminating the infection or averting it from transmission is rarely possible using anthelmintic groups of benzimidazole derivatives. Eugenol (EO) is the main extracted c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In the current study, the electron microscopy scans showed destruction of the normal structure of the cuticle of T. spiralis ML [ 26 , 27 ], expressed in the presence of areas with fissures and smoothing of the annulations ( Figure 5 A). Figure 5 B shows that the larva’s cuticle was severely damaged and destructured.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…In the current study, the electron microscopy scans showed destruction of the normal structure of the cuticle of T. spiralis ML [ 26 , 27 ], expressed in the presence of areas with fissures and smoothing of the annulations ( Figure 5 A). Figure 5 B shows that the larva’s cuticle was severely damaged and destructured.…”
Section: Resultsmentioning
confidence: 54%
“…Figure 5 B shows that the larva’s cuticle was severely damaged and destructured. These observations indicate the antinematodal effectiveness of the newly synthesized thiazinobenzimidazoles because the cuticle is the main route of drugs’ passage into the nematodes, with subsequent destruction of the larvae’s surface [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eugenol is naturally present in various aromatic plants such as nutmeg, Saigon cinnamon, and sweet basil ( ElGhannam et al, 2023 ). However, its primary natural source is Eugenia caryophyllata.…”
Section: Introductionmentioning
confidence: 99%
“…Clove is rich in a number of bioactive compounds, and eugenol is its major constituent with a content of about 4-14% (Ahmed et al, 2017;Irovetz et al, 2006;Neveu et al, 2010;Yun et al, 2010). Eugenol possesses a distinctive aroma, good antibacterial (Moemenbellah-Fard et al, 2020), anti-carcinogenic (Yassin et al, 2020), antioxidant (Sueishi and Nii, 2019), anti-inflammatory (Esmaeili et al, 2016), and anthelmintic properties (El Ghannam et al, 2023). Therefore, eugenol extracts from cloves are used extensively in food processing, primarily as a flavoring agent, preservative, and bactericide (Taleuzzaman et al, 2021;Yasuhiko and Fujii, 2011).…”
Section: Introductionmentioning
confidence: 99%